2001
DOI: 10.1016/s1055-3290(06)60169-6
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child Interaction in the Presence of Maternal HIV Infection

Abstract: This comparative study evaluated mother-child interaction in southeastern U.S. mother-child dyads where the mother was HIV positive and determined if the presence of maternal HIV infection was associated with differences in the quality of the mother-child interaction. A comparison was made between two groups of mother-child dyads, one where the mother was HIV positive (N = 25) and one where the mother was not HIV positive (N = 25). The Barnard model of mother-infant interaction guided this study. The quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These effects are clearly evident in the literature. For example, mothers who are HIV-positive are more likely to be clinically depressed than mothers who are HIV-negative (Johnson & Lobo, 2001). HIV-positive mothers also face a unique set of stressors in coping with their diagnosis and deciding whether or not to disclose their serostatus to their children.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are clearly evident in the literature. For example, mothers who are HIV-positive are more likely to be clinically depressed than mothers who are HIV-negative (Johnson & Lobo, 2001). HIV-positive mothers also face a unique set of stressors in coping with their diagnosis and deciding whether or not to disclose their serostatus to their children.…”
Section: Introductionmentioning
confidence: 99%
“…Many HIV‐positive mothers exhibited elevated depressive symptoms as a response to their diagnosis with a life‐threatening illness, their symptoms such as fatigue, pain, and gynecologic problems (Hudson et al, 2004; Miles, Burchinal, Holditch‐Davis, Wasilewski, & Christian, 1997), and their social problems such as poverty, social isolation, and stigma (Catz, Gore‐Felton, & McClure, 2002; Schrimshaw, 2003). HIV‐positive mothers reported higher depressive symptoms than HIV‐negative mothers (Morrison et al, 2002; Richardson et al, 2001), and HIV‐positive mothers have been shown to be less affectionate and less verbally responsive to their children than HIV‐negative mothers (Johnson & Lobe, 2001; Kotchick, Forehand, Brody, Armistead, & Morse, 1997; Murphy et al, 2002; Reyland, McMahon, Higgins‐Delessandro, & Luthar, 2002). HIV‐positive mothers reported that poverty and being single parents had a more negative influence on their parenting than did their HIV status (Swartz et al, 1998).…”
mentioning
confidence: 99%
“…According to Murphy 7 et al, 51% of the mothers with HIV infection met DSM-IV diagnostic criteria for a psychological disorder in the preceding year. Posttraumatic stress disorder and major depression [8][9] are the most commonly diagnosed psychological disorders among women with HIV infection.…”
Section: Introductionmentioning
confidence: 99%